Strategi Pelatihan Digital Marketing Untuk Peningkatan Daya Saing UMKM Di Media Sosial Dan Marketplace - Nisa Dienwati Nuris; Riri Narasati; Nuryadi; Riska Yati Ningrum (AMMA : Jurnal Pengabdian Masyarakat, 2024)
Micro, small, and medium enterprises (MSMEs) make a significant contribution to the economy, but often face obstacles in developing their business potential in the digital era. This Community Partnership Program aims to empower MSME entrepreneurs through the design of an integrated business ecosystem based on digital platforms. The implementation methods include analyzing the conditions of partner MSMEs, developing a relevant business ecosystem model design, intensive training on the utilization of digital platforms in various aspects of business operations (marketing, sales, inventory management, and customer interaction), and assistance in implementing the designed digital ecosystem. The expected outcomes of this program are improved operational efficiency, expanded market reach, strengthened customer relationships, and the promotion of sustainable business growth for partner MSMEs through the adoption of an effective digital ecosystem.